Women’s Empowerment: Bringing Women’s Rights and Health into Focus- A Comparative Analysis of State Fact Sheets of National Family Health Survey (NFHS)-4 & 5 - Mishra, Chhandasri; Dash , Shivangi; Pandey, Anuj Kumar; Mishra, Siddharth Sekhar (National Journal of Community Medicine, 2022)
Objectives: Women’s empowerment is a crucial factor for economic and social growth. India being committed to making women contribute equally to the growth and development of the country by 2030 (under Sustainable Development Goal-5), this study aimed to highlight the major shortcomings in the domain of Women’s health and other social and economic growth parameters. Methods: For this study, data related to various health and non-health parameters were used from largest survey in India i.e., National Family Health Survey factsheets. In reference to “the Global Gender Gap measure introduced by the World Economic Forum, the indicators have also been classified as 4 broad themes, for each of which, indicators were selected from NFHS factsheet for analysis, interpretation and reporting. Results: With 2.9% increase in the child sex ratio from 991 to 1022 females per 1000 males over the last two rounds of NFHS indicates a significant societal shift in the country. Out of 21 selected indicators, 4 parameters namely Screening test for cervical and breast cancer, Marriage of women before 18 years of age and Anaemia amongst women have shown a negative change over the past 5 years. Changes in the rural areas are more significant as compared with that of Urban areas. Conclusion: The study found that although, we have made some progress on the metrics around health, education, economic and social empowerment parameters, to get an adequate assessment of developments, we need to expand the basket of indicators and analyse change in them holistically.